The effect of CagA status on response to Helicobacter pylori eradication therapy - Murat SARUÇ; Gamze GÖKSEL; Sabriye ÖZKAYA; Feyzullah GÜÇLÜ; Beril ÖZBAKKALOĞLU; Hakan YÜCEYAR (Turkish Journal of Gastroenterology, 2019)
-